Too Complex to Work: A Critical Assessment of the Bail-in Tool under the European Bank Recovery and Resolution Regime. Issue 1 (22nd March 2018) - Tröger, Tobias H
ABSTRACT: This article analyses the bail-in tool under the European Bank Recovery and Resolution Directive (BRRD) and predicts that it will not reach its policy objective. To make this argument, this article first describes the policy rationale that calls for mandatory private sector involvement (PSI). From this analysis the key features for an effective bail-in tool can be derived. These insights serve as the background to make the case that the European resolution framework is likely ineffective in establishing adequate market discipline through risk-reflecting prices for bank capital. The main reason for this lies in the avoidable embeddedness of the BRRD's bail-in tool in the much broader resolution process which entails ample discretion of the authorities also in forcing PSI. Moreover, the idea that nearly all positions on the liability side of a bank's balance sheet should be subjected to bail-in is misguided. Instead, a concentration of PSI in instruments that fall under the minimum requirements for own funds and eligible liabilities (MREL) is preferable. Finally, this article synthesizes the prior analysis by putting forward an alternative regulatory approach that seeks to disentangle PSI as a precondition for effective bank-resolution as much as possible from the resolution process as such.